Analytical modeling of DSG in parabolic trough solar collectors - Oliveira, Carlos Antonio Alves de (2011)
Direct steam generation (DSG) in the absorber pipes of parabolic trough solar collectors is a promising procedure since the thermal fluid is water instead of thermal oil, as conventional solar concentrating systems use. It enables higher cycle temperatures and efficiencies, reducing the cost of the system. This paper presents an analytical model of (DSG) process in parabolic trough collectors. A collector row was divided in three sections and for each section a system of differential equations was derived. The model was implemented and simulations performed using a configuration and parameters similar to works published in the technical literature. Results of simulation have shown good agreement with them and allow obtaining many important parameters of the (DSG) process along the collector row: external and internal absorber temperature, fluid flow and temperature, vapor title and useful energy. A linear relationship between useful energy and collected irradiance has been obtained. Using the utilizability method, this result enables to make long term predictions about the system’s performance.